Welcome to Westonci.ca, your go-to destination for finding answers to all your questions. Join our expert community today! Explore thousands of questions and answers from a knowledgeable community of experts ready to help you find solutions. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
Let's go through each of the questions step-by-step using the provided function values from the table.
1. What is [tex]\( f(8) \)[/tex]?
Look for the value of [tex]\( f \)[/tex] when [tex]\( x = 8 \)[/tex] in the given table:
[tex]\[ f(8) = -7 \][/tex]
Thus, [tex]\( f(8) = -7 \)[/tex].
2. What is [tex]\( f^{-1}(-7) \)[/tex]?
To find [tex]\( f^{-1}(-7) \)[/tex], we need to determine the value of [tex]\( x \)[/tex] such that [tex]\( f(x) = -7 \)[/tex]. From the table, we see:
[tex]\[ f(8) = -7 \][/tex]
Therefore, [tex]\( f^{-1}(-7) = 8 \)[/tex].
3. What is [tex]\( f(6) \)[/tex]?
Look for the value of [tex]\( f \)[/tex] when [tex]\( x = 6 \)[/tex] in the table:
[tex]\[ f(6) = -3 \][/tex]
So, [tex]\( f(6) = -3 \)[/tex].
4. What is [tex]\( f^{-1}(-3) \)[/tex]?
To find [tex]\( f^{-1}(-3) \)[/tex], we need to find the value of [tex]\( x \)[/tex] such that [tex]\( f(x) = -3 \)[/tex]. According to the table:
[tex]\[ f(6) = -3 \][/tex]
Therefore, [tex]\( f^{-1}(-3) = 6 \)[/tex].
In summary, the answers are:
- [tex]\( f(8) = -7 \)[/tex]
- [tex]\( f^{-1}(-7) = 8 \)[/tex]
- [tex]\( f(6) = -3 \)[/tex]
- [tex]\( f^{-1}(-3) = 6 \)[/tex]
1. What is [tex]\( f(8) \)[/tex]?
Look for the value of [tex]\( f \)[/tex] when [tex]\( x = 8 \)[/tex] in the given table:
[tex]\[ f(8) = -7 \][/tex]
Thus, [tex]\( f(8) = -7 \)[/tex].
2. What is [tex]\( f^{-1}(-7) \)[/tex]?
To find [tex]\( f^{-1}(-7) \)[/tex], we need to determine the value of [tex]\( x \)[/tex] such that [tex]\( f(x) = -7 \)[/tex]. From the table, we see:
[tex]\[ f(8) = -7 \][/tex]
Therefore, [tex]\( f^{-1}(-7) = 8 \)[/tex].
3. What is [tex]\( f(6) \)[/tex]?
Look for the value of [tex]\( f \)[/tex] when [tex]\( x = 6 \)[/tex] in the table:
[tex]\[ f(6) = -3 \][/tex]
So, [tex]\( f(6) = -3 \)[/tex].
4. What is [tex]\( f^{-1}(-3) \)[/tex]?
To find [tex]\( f^{-1}(-3) \)[/tex], we need to find the value of [tex]\( x \)[/tex] such that [tex]\( f(x) = -3 \)[/tex]. According to the table:
[tex]\[ f(6) = -3 \][/tex]
Therefore, [tex]\( f^{-1}(-3) = 6 \)[/tex].
In summary, the answers are:
- [tex]\( f(8) = -7 \)[/tex]
- [tex]\( f^{-1}(-7) = 8 \)[/tex]
- [tex]\( f(6) = -3 \)[/tex]
- [tex]\( f^{-1}(-3) = 6 \)[/tex]
Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.